Study of the abrasiveness of rocks and its impact on drilling and consumption of bits and cutters. Colombian case (BISTUA Revista de la Facultad de Ciencias Básicas, 2022)
Abrasivity is one of the most important properties that influence the cost of processes such as drilling, blasting and comminution. This characteristic depends largely on the mineralogical composition, texture, structure and porosity of the rocks, characteristics that demand, for its determination, a careful petrographic examination, as well as the determination of the mechanical properties of compressive strength and indirect tensile strength of the rocks. But other more appropriate tests require the determination of the DRI, the CAI, the AVS and the CLI, among others.In our environment it is not very common to carry out these studies and when they are carried out, only those that require at most the petrographic study accompanied by the determination of the resistance properties of the intact material appear; however, today we have laboratories where the determination of the CAI can be carried out and when we have had to carry out more detailed studies such as the Tarkoy Hardness, for example, we have had to send the samples abroad.To disseminate these test methods, we undertook the task of refining, organizing and processing the results of a study we conducted in 2004 on the material exploited in a quarry located in the rock massif of northern Caldas, consisting of a Gneiss and a very abrasive and resistant Wollastonite Shale whose exploitation demanded a high cost in drilling and blasting.The study carried out on 14 Gneiss samples tested for AMC, VH, EQC, RAI, CAI, FSchim, LAC, HT, DRI, AVS, CLI and BWI abrasivities confirms this. Indeed, the material was found to have a high to extremely high abrasiveness, as well as a very high BWI, and a low to very low DRI and CLI.